Role of Perilipins in Oxidative Stress-Implications for Cardiovascular Disease - Mathieu Cinato; Linda Andersson; Azra Miljanovic; Marion Laudette; Oksana Kunduzova; Jan Borén; Malin C. Levin (MDPI AG, 2024)
Oxidative stress is the imbalance between the production of reactive oxygen species (ROS) and antioxidants in a cell. In the heart, oxidative stress may deteriorate calcium handling, cause arrhythmia, and enhance maladaptive cardiac remodeling by the induction of hypertrophic and apoptotic signaling pathways. Consequently, dysregulated ROS production and oxidative stress have been implicated in numerous cardiac diseases, including heart failure, cardiac ischemia-reperfusion injury, cardiac hypertrophy, and diabetic cardiomyopathy. Lipid droplets (LDs) are conserved intracellular organelles that enable the safe and stable storage of neutral lipids within the cytosol. LDs are coated with proteins, perilipins (Plins) being one of the most abundant. In this review, we will discuss the interplay between oxidative stress and Plins. Indeed, LDs and Plins are increasingly being recognized for playing a critical role beyond energy metabolism and lipid handling. Numerous reports suggest that an essential purpose of LD biogenesis is to alleviate cellular stress, such as oxidative stress. Given the yet unmet suitability of ROS as targets for the intervention of cardiovascular disease, the endogenous antioxidant capacity of Plins may be beneficial.